Echo: Efficient Complex Query over Dht Overlays - Hidalgo-Castillo, N (Academic Press, 2016)
In this article we propose ECHO, a novel and lightweight solution that efficiently supports range queries over a ring-like Distributed Hash Table (DHT) structure. By implementing a tree-based index structure and an effective query routing strategy, ECHO provides low-latency and low-overhead query searches by exploiting the Tabu Search principle. Load balancing is also improved reducing the traditional bottleneck problems arising in upper level nodes of tree-based index structures such as PHT. Furthermore, ECHO copes with DHT churn problems as its index exploits logical information as opposed to static reference cache approaches or replication techniques. The performance evaluation results obtained using PeerSim simulator show that ECHO achieves efficient performance compared other solutions such as the PHT strategy and its optimized version which includes a query cache. © 2015 Elsevier Inc.